40th Anniversary of Academic Council in Filatov Institute of Eye Diseases and Tissue Therapy (Ukrainian Journal of Ophthalmology, 2026)
I would like to start with a short excursus to the history. January, 13, 1934, Council of People's Commissars of the USSR enacted a regulation No79 “On academic degrees and titles” which established scientific degrees of Candidate of Science and Doctor of Science, scientific titles of Assistant, Associate Professor and Professor for Institution of Higher Education, scientific titles of a junior reserach fellow, a senior research fellow and a research fellow for Research Institutes (in 1937, the titles of assistant and junior research fellow were excluded from the list, merging from scientific rank to full-time positions in universities and research institutes). The same regulation implemented the system of conferment of an academic degree following the results of the public defense of candidate or doctoral dissertations, determined the requirements to persons seeking an academic degree and scientific title, “Procedure of conferment of an academic degree” and “Procedure of conferment of an academic title”.